Evaluation of Some Aspects of the Growth Parameters and Exploitation Rates of Deep-Water Rose Shrimp (Parapenaeus longirostris) from the Sea of Marmara - Ömerhan Dürrani; Habib Bal (Aquatic Sciences and Engineering)
The deep-water rose shrimp, Parapenaeus longirostris (Lucas, 1846) (Decapoda, Penaeidae) is economically significant due to its distinctive long rostrum and attractive pink-red colouring, playing a crucial role in marine ecosystems. This study investigated the length frequency, growth pattern, sex ratio, condition factor, von Bertalanffy growth parameters (L∞, 𝑘, t0), growth performance index (φ), exploitation rate, and mortality rates of deep-water rose shrimp. Samples were collected from commercial fishermen using beam trawl nets at depths of 60–110 m around the Kapıdağ Peninsula in the Sea of Marmara from September 2021 to April 2022 (excluding January). The minimum total lengths recorded were 58 mm for females and 68 mm for males. The total length-weight relationship exhibited positive allometry, whereas the carapace length-weight relationship showed negative allometry. The sex ratio did not deviate significantly from 1:1. The condition factor of females was significantly higher than that of males. The overall growth parameters, based on total length, were L∞ = 225.69 mm, 𝑘 = 0.14 year⁻¹, t0 = -0.17 year, and φ = 3.88. The estimated mortality rates were: total mortality = 0.83 year⁻¹, fishing mortality = 0.65 year⁻¹, natural mortality = 0.18 year⁻¹, and exploitation rate = 0.78. These findings provide valuable insights for the sustainable management of deep-water rose shrimp in the Sea of Marmara.